BPR Resilience in Economic Uncertainty: Comparison of BPR Financial Performance in Indonesia Before and During The Covid-19 Pandemic - Hakim, Lukman; Nurgupita, Rea Kanaya; Rizaldi, Muhammad; Zhahirah, Nasywa (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2024)
The primary objective of this study was to examine the performance of BPRs in Indonesia before and during the Covid-19 pandemic. The focus was on assessing financial performance variables, including Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL), Return on Asset (ROA), and Credit Disbursement. To achieve the study's objectives, a Descriptive Statistical Analysis was employed to provide a detailed overview of BPR performance during the two distinct periods. Additionally, a Difference Test, utilizing the Wilcoxon Test, was conducted to assess the significance of the differences observed between the pre-pandemic and pandemic periods. The results of the analysis revealed notable differences in the condition of BPRs before and during the Covid-19 pandemic. Significant changes were observed in financial performance variables such as NPL, ROA, and Credit Disbursement. However, LDR exhibited a tendency to be insignificant during this comparative analysis. It is crucial to acknowledge certain limitations in this study. The analysis focused primarily on financial performance variables, and other relevant factors may need consideration for a comprehensive understanding. Additionally, the study's findings are specific to the given time frame and may not account for potential longer-term effects. The identified differences in BPR performance provide valuable insights for policymakers and industry stakeholders. These findings can serve as a foundation for designing effective policies and strategies to address the economic impact of the pandemic. Moreover, the study offers essential insights for the banking industry, guiding them in adapting and building resilience in response to unexpected external changes.